Click chemistry decoration of amino sterols as promising strategy to developed new leishmanicidal drugs. - Porta, Exequiel Oscar Jesús (2014)
A series of 1,2,3-triazolylsterols was prepared from pregnenolone through reductive amination and copper(I)-catalyzed azide-alkyne cycloaddition (click chemistry). The newly generated stereocenter of the key propargylamino intermediate provided a mixture of diastereomers which were separated chromatographically, and the configuration of the R isomer was determined by X-ray crystallography. Ten triazolyl sterols were prepared, and the products and intermediates were screened in vitro against different parasites, with some compounds presenting IC50 values in the low micromolar range against Leishmania donovani